Resilient Regions from Sustainable Development Perspective - Szabó, Mariann; Csete, Mária Szalmáné; Pálvölgyi, Tamás (European Journal of Sustainable Development, 2018)
Regional economies in today‘s world of transitions experience different kinds of shocks: economic downturn, industry shocks which influence the path and pattern of regional economic growth, the quality of life of the inhabitants as well as the state of built and natural environment. Originated from ecological and psychological sciences the term ?resilience‘ describes the capability to adapt and renew under unfavourable conditions while regional resilience is determined how the region or system responds to shock or disturbance and under these circumstances able to ensure its continuous development. Continuous development criterion links regional resilience to sustainable development (improve the lives of people round the World) promoted by the 2030 Agenda for Sustainable Development and its 17 Sustainable Development Goals. Developing criteria for resilient regions for promoting sustainable development could contribute to more complex comprehension of regions in spatial development. The research, although put emphasis on economic viability regions are handled as complex systems of various institutional aspects, natural and man-made resources and society, which state, flexibility influences the adaptive capacity of regions to high extent. Keywords: Resilient Regions, Sustainable Development, Spatial Development, Sustainable Development Goals, Adaptive Capacity